2007
DOI: 10.1182/blood-2007-06-094565
|View full text |Cite
|
Sign up to set email alerts
|

Gαi2 is required for chemokine-induced neutrophil arrest

Abstract: Chemokines, including CXCL1, participate in neutrophil recruitment by triggering the activation of integrins, which leads to arrest from rolling. The downstream signaling pathways which lead to integrin activation and neutophil arrest following G-protein-coupled receptor engagement are incompletely understood. To test whether G␣ i2 is involved, mouse neutrophils in their native whole blood were investigated in mouse cremaster postcapillary venules and in flow chambers coated with P-selectin, ICAM-1, and CXCL1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
102
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 49 publications
1
102
0
Order By: Relevance
“…Moreover, increased blood monocyte numbers were noted in Ga i2 -deficient mice, whereas monocytes in the bone marrow (BM) are not affected (Ref. 22; data not shown). To determine the potential role of the individual Ga i proteins in the homing of monocytes and/or macrophages, we first examined whether the presence of Ga i2 and Ga i3 is needed for proper distribution of macrophages at different organ sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, increased blood monocyte numbers were noted in Ga i2 -deficient mice, whereas monocytes in the bone marrow (BM) are not affected (Ref. 22; data not shown). To determine the potential role of the individual Ga i proteins in the homing of monocytes and/or macrophages, we first examined whether the presence of Ga i2 and Ga i3 is needed for proper distribution of macrophages at different organ sites.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was shown that lack of Ga i2 leads to defects in the trafficking of T and B cells to lymph nodes (18,19) and in the recruitment of eosinophils and neutrophils to sites of inflammation (20,22,23). Moreover, increased blood monocyte numbers were noted in Ga i2 -deficient mice, whereas monocytes in the bone marrow (BM) are not affected (Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to selectin-mediated adhesion, which leads to the rolling of neutrophils, adhesion of leukocytes by b 2 integrins is firm and is regarded an essential step for transendothelial migration of inflammatory cells. b 2 -integrins are activated by chemokines such as CXCL1 (stored in small cytoplasmic granules) and CXCL8 (stored in Weibel-Palade bodies), which are secreted by endothelial cells (456,465). The binding of chemokines to chemokine receptors (CXCR1 and CXCR2) changes the conformation of integrins from bent to fully extended high-affinity configuration, enabling neutrophil arrest by binding to ICAM-1 that is expressed in endothelial cells (Fig.…”
Section: B Integrinsmentioning
confidence: 99%
“…The binding of chemokines to chemokine receptors (CXCR1 and CXCR2) changes the conformation of integrins from bent to fully extended high-affinity configuration, enabling neutrophil arrest by binding to ICAM-1 that is expressed in endothelial cells (Fig. 7b) (465). b 2 integrins are grouped into the categories according to the b subunit they contain.…”
Section: B Integrinsmentioning
confidence: 99%